Alternative Splicing From Abiotic Stress Tolerance to Evolutionary Genomics - Gao, Bei; Chen, Moxian; Oliver, Melvin J. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
A combination of dry lab bioinformatic analyses and wet lab molecular experiments seems to be a major trend for biological studies. The authors of the papers included in this reprint tried to elucidate the linkage between environmental stress and molecular response, and the species investigated in each of the articles are phylogenetically and agriculturally diverse. These exemplar studies will potentially ignite more ideas and biological stories to investigate gene functions.